HUBUNGAN LAMA KERJA DENGAN PAPARAN TIMBAL (PB) DALAM URINE PADA OPERATOR PERCETAKAN DI PT MANADO PERSADA MADANI - Abraham Momongan; Agus Rokot; Agnes T. Watung (Jurnal Kesehatan Lingkungan, 2019)
Lead (Pb) is a heavy metal that is naturally present in the earth’s crust and is spread through natural processes and comes from various human activities.Increased levels of Pb in the air as well as the working enviroment and industrial waste that uses Pb. Printing operators or employees are one of the groups exposed to lead (Pb). The purpose of this study was to determine the relationship of work duration with lead exposure (Pb) in urine on printing operator at PT Manado Persada Madani. This research is a quantitative study using observational analytic methods with cross sectional design. The sample in this study were all workers who served as printing operators, in sampling using cluster sampling techniques as many as 13 people by using two treatment of sampling namely before work and after work.Bivariate analysis research results were analyzed using the non parametric correlations test proving that there is a significant relationship between length of work with lead levels in printing operators with a correlation value = 0,852 with a strong correlation category. Statistically prove that there is a significant relationship between the length of work with lead levels in urine in printing operators who obtain P = 1,000 values.